The Influence of Brand Image, Digital Marketing, and Online Customer Reviews on Purchasing Decisions in the Skincare Industry - I Gusti Ayu Imbayani; I Made Surya Prayoga; Ni Komang Ayu Putri Dwiyanti (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
The Indonesian skincare industry has experienced rapid growth, with Somethinc emerging as one of the most popular local brands. Despite its earlier success, recent data indicate a decline in Somethinc’s market position, raising concerns about the factors influencing consumer purchasing behavior. This study aims to analyze the influence of brand image, digital marketing, and online customer reviews on purchasing decisions for the Somethinc brand in Denpasar City. A quantitative research design was employed, using purposive sampling to collect data from 119 respondents who had previously purchased Somethinc products. Data analysis was conducted with SPSS version 26.0 to test the proposed hypotheses. The results show that brand image has a significant positive effect on purchasing decisions (? = 0.680; p 0.05), digital marketing also exerts a significant positive effect (? = 0.178; p 0.05), and online customer reviews significantly enhance purchasing decisions (? = 0.255; p 0.05). These findings highlight the importance of strengthening brand perception, optimizing digital marketing strategies, and managing online reviews to sustain consumer trust and market competitiveness.